1986
DOI: 10.1152/jappl.1986.60.3.1011
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory acclimatization to hypoxia is not dependent on cerebral hypocapnic alkalosis

Abstract: We previously demonstrated that, in awake goats, 6 h of hypoxic carotid body perfusion during systemic normoxia produced time-dependent hyperventilation that is typical of ventilatory acclimatization to hypoxia (VAH). The hypocapnic alkalosis that occurred could have produced VAH by inducing cerebral vasoconstriction and brain lactic acidosis even though systemic arterial normoxia was maintained. In the present study we tested the hypothesis that hypocapnic alkalosis is a necessary component of VAH. Goats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…The ⌬V E/⌬PET O 2 is considered by many investigators to be indicative of peripheral chemoreflex sensitivity (8,9,44). Accordingly, our findings might suggest that chemoreflex sensitivity was decreasing from the initial to the final hypoxic episode.…”
Section: Women Mensupporting
confidence: 52%
“…The ⌬V E/⌬PET O 2 is considered by many investigators to be indicative of peripheral chemoreflex sensitivity (8,9,44). Accordingly, our findings might suggest that chemoreflex sensitivity was decreasing from the initial to the final hypoxic episode.…”
Section: Women Mensupporting
confidence: 52%
“…Six hours of isolated carotid body hypoxia caused a progressive increase in ventilation above the acute hypoxic ventilatory response (Busch et al, 1985). Such time-dependent changes in ventilation did not occur with (a) 6 hours of carotid body hypercapnia (Bisgard et al, 1986a), (b) 4 hr of systemic hypocapnia (Bisgard et al, 1986b) or, (c) systemic arterial hypoxia (Weizhen et al, 1992). These results show the response is specific to carotid body hypoxia and not the result of increased carotid body stimulation or activity, or changes in P O 2 or pH at central chemoreceptors and respiratory centers in the brain.…”
Section: Plasticity In Carotid Bodymentioning
confidence: 95%
“…It was first shown that 4-6 h of steady-state hypoxic CB perfusion (Po2 = 40 Torr) during systemic normoxia (brain normoxia) could produce time-dependent hyperventilation that is indistinguishable from that produced by systemic hypoxia in awake goats [16][17][18]. Thus, ventilatory acclimatization could be in duced in the absence of brain hypoxia and stimulation of the CB alone could induce acclimatization.…”
Section: Cb Function In Acclim Atization To Hypoxiamentioning
confidence: 99%